Sejrskode, økonomi og politik som begrundelse for sundhedsfare og regelbrud - doping-historie og doping i DDR - Spitzer, Giselher (Forum for Idræt, 2001)
Dopinghistorien som normativ og rekonstruerbar. Victory code, economics and politics as grounds for health dangers and infringement of rules – the history of doping and doping in the DDR Doping has a history – and that history can be reconstructed. This emerges from a sports science report on what was in part a depressing past in the DDR. This recognition, however, gives also cause for cheer. Like the historical debate in Germany about the understanding of sport under National Socialism, systems of doping and sports in the DDR, the pros and contras of the doping debate, have special significance. Recognition of normative tendencies (such as the Frankfurt school’s) permit at the same time also a value judgement and in that way provide help in not repeating mistakes already committed. In the best instances it can even succeed in correcting structural defects. Contemporary history as critical social science has an express enlightening role here and can at the same time to a considerable extent be action-oriented. That is to say, that its results can be used in practice.